2004
DOI: 10.1021/ja0452020
|View full text |Cite
|
Sign up to set email alerts
|

Two-Photon Photosensitized Production of Singlet Oxygen in Water

Abstract: Singlet molecular oxygen (a(1)Delta(g)) has been produced and optically detected in time-resolved experiments upon nonlinear two-photon excitation of a photosensitizer dissolved in water. For a given sensitizer, specific functional groups that impart water solubility and that give rise to larger two-photon absorption cross sections are, in many cases, not conducive to the production of singlet oxygen in high yield. This issue involves the competing influence of intramolecular charge transfer that can be pronou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
174
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 171 publications
(186 citation statements)
references
References 55 publications
12
174
0
Order By: Relevance
“…35 The absorption spectrum of TMPyP, which is typical of porphyrins, is shown in Figure 2. Singlet oxygen can be produced upon irradiation into either the intense Soret band at ~ 420 nm or the weaker Q-band system over the range 500-600 nm.…”
Section: General Characterization Of Tmpyp and Chlmentioning
confidence: 99%
“…35 The absorption spectrum of TMPyP, which is typical of porphyrins, is shown in Figure 2. Singlet oxygen can be produced upon irradiation into either the intense Soret band at ~ 420 nm or the weaker Q-band system over the range 500-600 nm.…”
Section: General Characterization Of Tmpyp and Chlmentioning
confidence: 99%
“…This suggested that the reaction might perhaps be run in aqueous solvent mixtures, with corresponding benefits in the context of green chemistry. Even though reactions involving photochemically generated 1 O 2 in the presence of H 2 O have occasionally been reported, [32][33][34] the use of aqueous solutions in preparative photochemistry has been largely overlooked, probably because water and other protic solvents are excellent quenchers which reduce the lifetime of 1 O 2 . 35,36 With these facts in mind, the effect of the presence of 3 on the emission lifetimes of Conducting the photo-oxidation of 3 with O 2 (0.1 MPa) in mixtures of THF or EtOH with H 2 O and water-soluble photosensitizers confirmed this finding; indeed, the yields of 1 were similar to those obtained in DCM and in one case higher (see Table 2, entry 2).…”
Section: Strategy 2: Reactions In Aqueous Mixtures Of Organic Solventsmentioning
confidence: 99%
“…However, the currently used systems (porphyrins and tetrapyrroles) are poor two-photon absorbers [54] and only very few examples can be found in the literature. First attempts relied on the use of the meso-substituted and water-soluble porphyrins with two-photon absorption cross-section (s TPA ) of the order 100 Göppert-Mayer (1 GM ¼ 10 À50 cm 4 s photon À1 molecule À1 ) in the near infrared [55]. In order to increase s TPA values via antenna effect, these porphyrins have been incorporated into two-photon chromophore-based dendrimers.…”
Section: Singlet Dioxygen Generation For Photodynamic Therapy (Pdt) Omentioning
confidence: 99%